Pendidikan Nilai Karakter Pada Mata Pelajaran Ilmu Pengetahuan Sosial - Handayani, Handayani - (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2024)
The researcher hopes that character education can help children become kind individuals, responsible community members, and conscientious citizens. This will enable them to recognize signs of moral crises and contribute to nurturing the next generation. Social Studies (IPS) education can address various issues related to character development in students at Madrasah Ibtidaiyah Negeri 3 in Banda Aceh City. A qualitative-descriptive method was used in this study to explore the principles and nature of social studies (IPS). The analysis of the research explains the role of IPS education in students' development, highlighting how it helps them face more challenging lives by learning to interact positively with others in the modern world. The same applies to Madrasah Ibtidaiyah Negeri 3 in Banda Aceh City. Character education must be instilled from an early age, beginning at the elementary school level. Students who receive IPS education will develop strong morality, good character, and a solid foundation of religious knowledge. Building character education is essential for the future sustainability and prosperity of the nation. For progress to be achieved, a well-designed plan, the right strategies, and effective teaching techniques are crucial. In elementary schools, the goal of IPS education is to provide basic knowledge and skills that are useful for daily life.Keywords: Education, Social Studies, Character Education.